Determinants Of Cloud Accounting Adoption Intention: The T.O.E, D.O.I and T.A.M. Models - Ismail Ouaadi; Mohammed El Haddad (Journal of Accounting Research, Organization and Economics, 2021)
Objective – Nowadays, Cloud Computing is a necessity and more than a trend for all or-ganizations, given the sensitive nature of financial information. This paper aims to determine the factors that impact the adoption intention of Cloud Accounting.Design/methodology – The approach adopted in this research is a quantitative method. It is based on a research model developed on the basis of three theoretical frameworks (TOE, DOI, and TAM) used to investigate the factors impacting the adoption intention of Cloud Ac-counting solutions by accounting professionals (with a total number of respondents of 96 and composed by chartered accountant, certified public accountant, and accountant).Results – The results of this study show that some variables have an impact on the inten-tion to adopt Cloud Accounting, such as the purpose of usage, motivation, remote reporting, and size of the firm, while other variables have no influence such as professional category and flexibility.Limitation/Suggestion – The major contributions of this work are: (1) The combina-tion of several theoretical frameworks; (2) The application in the field of organizational fi-nance which is very important in terms of business and sensitivity, and finally the highlight-ing of the factors leading to the adoption of Cloud Accounting.